Comprobación forense del método de espectrofotometría de absorción atómica para determinar plomo (Pb) y antimonio (Sb) impregnados en la mano después de disparar una arma de fuego, 2013. - Reina Alminate, Robertha T (2014)
Firearms have been created with the purpose of causing harm, using a projectile (bullet) and yielding his in the body for this reason it is necessary to clarity them, for it introduced elements determining residues Lead (Pb) and Antimony (Sb) impregnated in the hands of the shooter of a firearm by atomic absorption spectrophotometry. This research work has been done in seven chapters.